Mild Ring‐Opening 1, 3‐Hydroborations of Non‐Activated Cyclopropanes. Issue 51 (21st November 2018) - Wang, Di; Xue, Xiao‐Song; Houk, Kendall N.; Shi, Zhuangzhi
Abstract: The Brown hydroboration reaction, first reported in 1957, is the addition of B−H across an olefin in an anti‐Markovnikov fashion. Here, we solved a long‐standing problem on mild 1, 3‐hydroborations of non‐activated cyclopropanes. A three‐component system including cyclopropanes, boron halides, and hydrosilanes has been developed for borylative ring‐opening of cyclopropanes following the anti‐Markovnikov rule, under mild reaction conditions. Density functional theory (M06‐2X) calculations show that the preferred pathway involves a cationic boron intermediate which is quenched by hydride transfer from the silane. Abstract : A mild three‐component system was developed for the preparation of alkylboronic esters by ring‐opening 1, 3‐hydroborations of non‐activated cyclopropanes. This method has good functional group compatibility and can serve as a powerful synthetic tool for late‐stage borylative ring‐opening of cyclopropanes in complex compounds.